2017
DOI: 10.1080/13880209.2017.1304428
|View full text |Cite
|
Sign up to set email alerts
|

Inter-species comparative antioxidant assay and HPTLC analysis of sakuranetin in the chloroform and ethanol extracts of aerial parts of Rhus retinorrhoea and Rhus tripartita

Abstract: Context: Extensive research on Rhus (Anacardiaceae) shows their antioxidant potential, which warrants further evaluation of its other species.Objective: To perform a comparative antioxidant assay on extracts of R. retinorrhoea and R. tripartita, including sakuranetin quantification by a validated HPTLC method.Materials and methods:In vitro antioxidant assay was performed on chloroform and ethanol extracts of R. retinorrhoea Steud. ex Oliv. (RRCE and RREE) and R. tripartita (Ucria) Grande (RTCE and RTEE) by DPP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Therefore, in the present study, the promising antioxidant activity of R. tripartita fruits might be conferred by phenolic compounds identified through LC-MS/MS analysis. These findings were supported by other studies on R. tripartita fruits, which reported that its high antioxidant property was related to richness in flavonoids, especially flavones [8].…”
Section: In Vitro Antioxidant Assays Analysissupporting
confidence: 85%
See 1 more Smart Citation
“…Therefore, in the present study, the promising antioxidant activity of R. tripartita fruits might be conferred by phenolic compounds identified through LC-MS/MS analysis. These findings were supported by other studies on R. tripartita fruits, which reported that its high antioxidant property was related to richness in flavonoids, especially flavones [8].…”
Section: In Vitro Antioxidant Assays Analysissupporting
confidence: 85%
“…Several biological activities of R. tripartita fruit have been attributed to the richness of phenolic compounds [15]. As a result, in recent years there is a growing interest in the extraction of phenolic compounds from edible R. tripartita fruit to be used in food, nutraceutical and pharmaceutical products [8].…”
Section: Introductionmentioning
confidence: 99%
“…In Figure 3. the results of thick extracts from the organic solvent extraction process combined with ultrasonic [32,33,34] then dissolved in methanol and injected on HPLC obtained standard Polyphenon retention time chromatogram which was the same as callus extract sample retention time. It can be said that the Camellia sinensis L callus contains bioactve Polyphenon ACKNOWLEDGEMENT The author would like to acknowledge the Indonesian Directorate General of Research Technology and Higher Education, which has funded this research trough Competition Grants.…”
Section: E Identification Of Polyphenon From Camellia Sinensis L Callusmentioning
confidence: 99%
“…Sumac is the common name for a genus (Rhus) that contains over 250 individual species of flowering plants in the family Anacardiaceae [3]. Traditional species of Rhus used to manage several ailments including influenza, wounds, diarrhea, abdominal pain, indigestion, diabetes, malaria, rheumatism, aching gums, toothaches, swollen legs, dog bites, peptic ulcer, kidney stones, skin eruptions, bruises, and boils [5,6]. R. vulgaris in Ethiopia is used to treat various diseases according to Ethno-botanically or Ethno-pharmacological studies?…”
Section: Introductionmentioning
confidence: 99%